Crowdsourcing and language learning habits and practices in Turkey, Bosnia and Herzegovina, the Republic of North Macedonia and Poland in the pre-pandemic and pandemic periods - Çiler Hatipoğlu; Nihada Delibegović Džanić; Elżbieta Gajek; Lina Miloshevska (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave)
The popularity of online crowdsourcing platforms was slowly increasing among language learners before the pandemic, but COVID-19 changed the educational systems worldwide. This study aims to uncover whether or not, and if ‘YES’, how the attitudes and habits of language learners concerning the use of crowdsourcing materials in Turkey, Bosnia and Herzegovina, the Republic of North Macedonia and Poland changed during the pandemic.